2013
DOI: 10.1016/j.ijgo.2012.12.014
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the impact of malaria prevention in pregnancy on low birth weight and maternal anemia

Abstract: Although randomized trials have demonstrated the efficacy of SP, studies evaluating scale-up programs found less consistent reductions in LBW and maternal anemia. Additional strategies to improve SP coverage may reduce the LBW and maternal anemia associated with malaria in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 38 publications
4
49
0
3
Order By: Relevance
“…Due to the adverse effects of malaria infection in pregnancy, recommendations have been made to use insecticide treated mosquito nets and prophylactic drugs such as sulfadoxine pyrimethamine. The use of these measures have brought reductions in anaemia and low birth weight delivery in pregnant women [28, 29]. There were some limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the adverse effects of malaria infection in pregnancy, recommendations have been made to use insecticide treated mosquito nets and prophylactic drugs such as sulfadoxine pyrimethamine. The use of these measures have brought reductions in anaemia and low birth weight delivery in pregnant women [28, 29]. There were some limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies however reported a significant decline in prevalence following PAM control interventions. The protection of joint ITNs with IPTp-SP use is significant in only certain trials, yet reported ITN use ranges from 5 to 25%, and this might not be sufficient enough to show an effect [60]. An article reviewed the influence of preventive measures on PAM during a decade, effectively 2002 to 2012, and reported placental malaria rates ranging from 2 to 29% among women treated with less than three doses (mainly two) of sulphadoxine-pyrimethamine (SP) compared to 2 to 8% among women receiving more than or equal three doses (mainly three) [60].…”
Section: Methods: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…The protection of joint ITNs with IPTp-SP use is significant in only certain trials, yet reported ITN use ranges from 5 to 25%, and this might not be sufficient enough to show an effect [60]. An article reviewed the influence of preventive measures on PAM during a decade, effectively 2002 to 2012, and reported placental malaria rates ranging from 2 to 29% among women treated with less than three doses (mainly two) of sulphadoxine-pyrimethamine (SP) compared to 2 to 8% among women receiving more than or equal three doses (mainly three) [60]. A novel study included within the afore mentioned review describes a two-fold lower prevalence of placental malaria in the three-dose SP group compared to the two-dose SP group (adjusted prevalence ratio = 0.48) [61].…”
Section: Methods: Search Strategy and Selection Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Although guidelines recommend that HIV-positive women who are pregnant receive CTX without SP, real-world application of HIV and malaria guidelines in pregnancy suggests that HIV-positive women are receiving both ART and SP, with or without CTX. 15 SP has been associated with a decreased risk of low birth weight (LBW) among pregnant women in general [16][17][18] and among HIV-infected pregnant women in specific. 19 A Cochrane review of trials comparing dosing regimens found that infants born to HIV-positive pregnant women receiving three or more doses of SP weighed more than those born to mothers receiving two doses.…”
Section: Introductionmentioning
confidence: 99%